The Role of Mitochondrial DNA Damage and Repair in the Resistance of BCR/ABL-Expressing Cells to Tyrosine Kinase Inhibitors - Glowacki, Sylwester (MDPI, 2013)
Chronic myeloid leukemia (CML) is a hematological malignancy that arises from the transformation of stem hematopoietic cells by the fusion oncogene BCR/ABL and subsequent clonal expansion of BCR/ABL-positive progenitor leukemic cells. The BCR/ABL protein displays a constitutively increased tyrosine kinase activity that alters many regulatory pathways, leading to uncontrolled growth, impaired differentiation and increased resistance to apoptosis featured by leukemic cells. Current CML therapy is based on tyrosine kinase inhibitors (TKIs), primarily imatinib, which induce apoptosis in leukemic cells. However, some patients show primary resistance to TKIs while others develop it in the course of therapy. In both cases, resistance may be underlined by perturbations in apoptotic signaling in leukemic cells. As mitochondria may play an important role in such signaling, alteration in mitochondrial metabolism may change resistance to pro-apoptotic action of TKIs in BCR/ABL-positive cells. Because BCR/ABL may induce reactive oxygen species and unfaithful DNA repair, it may affect the stability of mitochondrial DNA, influencing mitochondrial apoptotic signaling and in this way change the sensitivity of CML cells to TKIs. Moreover, cancer cells, including BCR/ABL-positive cells, show an increased level of glucose metabolism, resulting from the shift from oxidative phosphorylation to glycolysis to supply ATP for extensive proliferation. Enhanced level of glycolysis may be associated with TKI resistance and requires change in the expression of several genes regulated mostly by hypoxia-inducible factor-1α, HIF-1α. Such regulation may be associated with the impaired mitochondrial respiratory system in CML cells. In summary, mitochondria and mitochondria-associated molecules and pathways may be attractive targets to overcome TKI resistance in CML.